Impact Leadership Head School and Professionality Teachers on the Performance of Primary School Teachers in the Pattimura Group Rakit District Banjarnegara - Toni Wahyudi (UM Purwokerto Press, 2025)
This study aims to determine the relationship between Principal leadership, professionalism, and teacher performance. This type of research is ex-post facto with a quantitative approach. The dependent variable in this study is Teacher Performance. The independent variables in this study are Principal Leadership and Teacher Professionalism. The respondents of this study were elementary school teachers in Gugus Pattimura, Rakit District, Banjarnegara Regency. Data collection techniques used observation, questionnaires and documentation. The results of this study indicate that: (1) Principal leadership has a positive effect on teacher performance of 15.7% based on (R Square) of 0.157; (2) Teacher professionalism has a positive effect on teacher performance of 26.3% based on (R Square) of 0.263; (3) Principal Leadership and Teacher Professionalism together have a positive effect on Teacher Performance of 35% based on (R Square) of 0.350. Based on the results of the research that has been conducted, the variables of Principal Leadership and Teacher Professionalism should be improved in order to improve teacher performance.